Poster Media Strategies For Building Religious Tolerance In Bangsri Village - Sholikhatun Khasanah; Muhamad Rifa'i Subhi (Moderatio: Jurnal Moderasi Beragama, 2025)
This article examines the development of poster media as an educational tool to instill the values of religious moderation in Bangsri Village. Religious moderation is an important concept in maintaining harmony, tolerance and harmony in a pluralistic society. The purpose of this study is to determine the effectiveness of poster media in conveying religious moderation messages to teenagers as a group that is vulnerable to being exposed to intolerance. The method used is qualitative research with data collection techniques through field observations, in-depth interviews with community leaders and teenagers, and literature studies related to moderation values. The results showed that poster media has high visual appeal, is easily understood by various groups, and is able to reach a wide range of public spaces. The developed posters contain core messages of religious moderation such as the importance of tolerance, mutual respect for differences, and rejection of all forms of violence and extremism in the name of religion. The poster design also considers the local context to make it more relevant to the lives of local communities. The findings show that poster media can be an effective communication strategy in religious education, especially in building youth awareness of the importance of peaceful coexistence in diversity.